The National Innovation System (NIS) and the automobile industry in South Korea - Ji Yoon Chung (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
Since Freeman (1988) suggested the concept of National Innovation System (NIS), NIS has provided a foundation for understanding the organizational interactions that engendered innovations in industry. The definition of NIS varies with the context in which innovation activities are performed and evaluated. The multiple definitions of NIS can be classified by their scopes (Chung 2002). In a broad sense, NIS encompasses all the interrelated institutional actors that create, diffuse, and exploit innovations. On the contrary, according to the narrow definition, NIS is a complex of innovation actors that are only directly associated with the generation, diffusion, and appropriation of technological innovation. Research and Development (R&D) departments, universities, and public research institutes can be taken as examples. In this report, primarily the narrow definition of NIS will be adopted, and the role of NIS in the South Korean automotive industry will be accordingly discussed.
urn:nbn:de:0011-n-1866338
Keywords: 330